Thinking and Self-Absorption: José Ortega y Gasset, Hannah Arendt and the problem of judging a technological world - Castleton, Alexander (Anales del Seminario de Historia de la Filosofía, 2024)
José Ortega y Gasset and Hannah Arendt were two thinkers for whom the ability to self-absorb and judge the circumstance was essential on both a personal and social level. In a world increasingly mediated by digital technologies that transform the individual into something measurable, predictable, and controllable due to the data that is left with its use, it is essential to think and judge how we want our life to be with these technologies. In addition, it is necessary to demonstrate to others our capacity for agency and decision in the face of technical circumstances.
Keywords: Hannah Arendt; José Ortega y; Technology; Self-Absorption; Thinking; Judging